Rapid and sustained improvements in itch and quality of life with upadacitinib plus topical corticosteroids in adults and adolescents with atopic dermatitis: 52-week outcomes from the phase 3 AD Up study - Nina Magnolo; Michael C. Cameron; Mona Shahriari; Bob Geng; Brian M. Calimlim; Henrique Teixeira; Xiaofei Hu; Yang Yang; Yingyi Liu; Shiyu Zhang; Cristina Sancho Sanchez; Katherine Altman; et al. (Taylor & Francis Group, 2024)
AbstractPurpose: Atopic dermatitis (AD) adversely impacts quality of life (QoL). We evaluated the effect of upadacitinib, an oral selective Janus kinase inhibitor approved for moderate-to-severe AD, plus topical corticosteroids (+TCS) on patient-reported outcomes (PROs) over 52 weeks.Materials and methods: In the phase 3 AD Up study (NCT03568318), adults and adolescents with moderate-to-severe AD were randomized 1:1:1 to once-daily upadacitinib 15 mg, 30 mg, or placebo + TCS. Itch, skin pain/symptoms, sleep, QoL, daily activities, emotional state, mental health, and patient impressions of disease severity/improvement/treatment satisfaction were assessed.Results: This analysis included 901 patients. Within 1-2 weeks, PRO improvements were greater with both upadacitinib doses than with placebo (p <.05). Improvements increased through weeks 4-8; rates were generally maintained through week 52. At week 52, the proportion of patients with clinically meaningful improvements in itch (Worst Pruritus Numerical Rating Scale improvement ≥4), skin pain (AD Symptom Scale Skin Pain improvement ≥4), sleep (AD Impact Scale [ADerm-IS] Sleep improvement ≥12), daily activities (ADerm-IS Daily Activities improvement ≥14), and emotional state (ADerm-IS Emotional State improvement ≥11) ranged from 62.1%-77.7% with upadacitinib 15 mg + TCS and 71.3%-83.6% with upadacitinib 30 mg + TCS.Conclusions: Upadacitinib + TCS results in rapid, sustained improvements in burdensome AD symptoms and QoL.